Understanding Dynamics of Food Insecurity and Vulnerability in Chepang Community - Gurung, Chan Bahadur (Journal of Advanced Academic Research, 2022)
Chepangs are one of the highly marginalized indigenous peoples of Nepal who are vulnerable in terms of food security and have been living in environments characterized by high risk of various shocks. This study examines the dynamics of food insecurity and vulnerability in Chepang community. The study uses a mixed method approach. Data were obtained by using semi structured household questionnaire and key informant interview checklist. The household questionnaire included modules on household demographics, migration, housing facilities, assets and access to credit facilities, agriculture, income, expenditure, food sources and consumption patterns, shocks and food security. The questionnaire also contained questions on maternal and child health and nutrition. For child anthropometry, height and weight were also measured of all children below 5 years (6-59 months). About 90 percent of the sampled households reported food insecurity. Overall, assets deprivation, recurrent phenomena of covariate and idiosyncratic shocks, unfavorable state policies, and socio-cultural factors, low profile of education, larger family size, lack of income, higher expenditure on foods, low consumption patterns, and poor access to health care, water and sanitation facilities etc. are the major determinants of vulnerability of households to food insecurity. These factors were, in turn, determined by the poor resource endowment of the household which they could pursue in meeting their income and food security objectives. 75 percent of expenditure of Chepang households goes to food purchase. This high food expenditure share means that resources and incomes available to the households devotes to food indicating poor access to food. Again, more than 53 percent of the households belongs to the very poor and poor food consumption groups. This means suffering from food energy deficiencies, low dietary diversity, deriving more energy from staples, lacking micronutrients and having very poor and poor consumption patterns and poor food security status. The main coping strategies being adopted include unskilled wage laboring, collection, consumption and marketing of forest foods and products, sales of livestock animals, borrowing money and changing consumption patterns in the study area. This ethnicity based analysis could be of great value to the government, non-governmental organizations and development agencies in the design of effective food security strategies and development programs as policy response both now and in the future.